Živim v Bukovem Vrhu pod Bukovim vrhom O spremembi pravopisnega pravila za pisanje zemljepisnih imen - Černivec, Manca; Dobrovoljc, Helena; Geršič, Matjaž (ZRC SAZU, Založba ZRC, 2020)
The monograph ('I live in Bukov Vrh ('village') below Bukov vrh ('hill')') contains eight different proposals for writing the initial in the non-first components of multi-word geographical proper names. The proposals were presented at the open conference ""Meeting of two commissions"" in June 2019. The motives that triggered the discussion on spelling reform and the decision to consult with the general public before the final decision of the spelling commission are presented. A survey will be prepared, presenting the views of the debaters, presented in the present monograph. The views of the chapters in the central part of the monograph can be summarized in three groups: the first group advocates a more comprehensive reform, which is reflected in the technical solution of writing geographical names - ""all components of the name with a capital letter""~the second group does not advocate technical reform at the outset, but focuses on clarifying the rules and abolishing the division into settlement and non-settlement names~the third group does not support any changes.